A Rare Orthopedic Emergency: Both Fracture-Dislocation of the Shoulder and Hip in a Patient - Gurger, Murat; Gurger, Mehtap; Batur, Omer Cihan; Celik, Suat; Atescelik, Metin (Aves, 2015)
Introduction: Traumatic fracture-dislocations of the shoulder and hip are serious injuries caused by high-energy trauma and can lead to long-term morbidity. Case Report: In this case report, we present a case of rare orthopedic emergency due to right hip dislocation, acetabular fracture, pertrochanteric femoral fracture, left inferior shoulder dislocation, and left proximal humerus fracture in a 72-year-old male patient suffering from a traffic accident that occurred while the patient was sitting inside the car. Conclusion: The occurrence of both inferior shoulder dislocation with fracture (luxatio erecta) and fracture-dislocation of the hip are extremely rare and have not been described previously in a single patient. Rates of complications and additional injuries are high in both situations.
Keywords: Dislocation; fracture; shoulder; hip